2020
DOI: 10.18535/ijmsci/v7i04.03
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Association Between Oral Hygiene and the Development of Tonsillitis or Tonsillar Hyperplasia

Abstract: Background: The number of recurrent tonsillitis and tonsillar hyperplasia requiring tonsillectomies, annually is huge. Poor oral hygiene has been linked with the occurrence of these tonsillar diseases.  Objective: To determine the association between poor oral hygiene and tonsillitis and/or tonsillar hyperplasia. Methodology: This was a study of association between oral hygiene and tonsillitis and/or tonsillar enlargement determined by correlating the Oral hygiene index scores (OHIS) and Decay Miss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
1
0
3
Order By: Relevance
“…We observed that the mean age of the TT group was significantly higher than TC. This result may be associated with the frequent occurrence of chronic tonsillar inflammation in older adults because of the risk factors like smoking and poor oral hygiene [21, 22]. Oral bacteria in secretions in contact with tonsillar epithelium may adhere to the mucosal surface and may stimulate cytokine production by mucosal epithelium [23].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the mean age of the TT group was significantly higher than TC. This result may be associated with the frequent occurrence of chronic tonsillar inflammation in older adults because of the risk factors like smoking and poor oral hygiene [21, 22]. Oral bacteria in secretions in contact with tonsillar epithelium may adhere to the mucosal surface and may stimulate cytokine production by mucosal epithelium [23].…”
Section: Discussionmentioning
confidence: 99%
“…[26], [27] Sebanyak 3 artikel memiliki desain studi case control retrospektif dan 1 artikel dengan desain studi clinical trial. [8], [28]- [30]…”
Section: Metode Penelitianunclassified
“…Bakteri Moraxella catarrhalis merupakan bakteri yang sering ditemukan pada saluran pernapasan bagian atas (nasofaring) yang berdekatan dengan tonsil. [28] Kansu et al (2017) mengutarakan bakteri Actinomyces lebih menonjol pada pasien dewasa dengan hipertropi tonsil. Bakteri Actinomyces merupakan bakteri yang sering ditemukan pada daerah orofaring yang merupakan tempat tonsil palatina palatina.…”
Section: Halitosis As An Indicationunclassified
See 1 more Smart Citation